Pemahaman dan Tanggung Jawab Umat dalam Melestarikan Lingkungan di Stasi Santa Maria Long Lanuk - Theresia Ping; G. Simon Devung; Gregorius Verensius Era (Gaudium Vestrum - Jurnal Kateketik Pastoral, 2017)
This study aims to get the illustration about the comprehension of the Catholics at the Church-station of Santa Maria Long Lanuk about the conservation of the environment and their responsibility in conserving local environment. The subjects or the respondents in this study were the Catholics who settling in the Church-station of Santa Maria Long Lanuk, the Parish of Santo Eugenius de Mazenod Tanjung Redeb, in the Subdistrict of Sambaliung, the Regency of Berau, East Kalimantan Province. The objects of the study were the comprehension and the responsibility. The methods used in collecting the data were direct observation on the local home and forest environment, structured interviews and documentation study. Based on the result of the study and the collection of the field data, the researcher found that the comprehension the Catholics at the Church-station of Santa Maria Long Lanuk about the conservation of the environment and their responsibility in conserving local environment, are as the following: 65% of the Catholics have sufficient comprehension and responsibility, 25% have less comprehension and 5% though do not have sufficient comprehension but responsible, and 5% do not have sufficient comprehension and also not responsible. Based on the quadrant analysis, the hypothetic proposition which can be conveyed is: that the comprehension needed is the comprehensive understanding because it is not enough to have only the cognitive comprehension, but also the affective and psychomotoric comprehension. Therefore, the assumption that, the higher comprehension someone has the more responsible he is, does not occur for the Catholics at the Church-station of Santa Maria Long Lanuk; because, from the quadrant analysis it is found that, there are Catholics who have less comprehension but responsible. As the recommendation of this study: the group members who comprehend and are responsible can become the motivators in the effort of conserving the environment; the group members who do not have sufficient comprehension but responsible, need to be assisted by giving them the catechesis about the conservation matters and responsibility in conserving the environment; while the group members who do not understand and also are not responsible, needs special assistance by giving them the catechesis about the conservation matters and responsibility in conserving the environment, and involving them as activators in the efforts of conserving the environment.